2018
DOI: 10.28991/cej-03091187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Strength behaviour of Cement-RHA Stabilized and Polypropylene Fiber Reinforced Clay-Sand Mixtures

Abstract: In this paper, regarding the high availability of rice husk ash (RHA) in Guilan province, also, to decrease the geo-environmental issues caused by dumping RHA in the environment, different clay-sand mixtures are stabilized using the combination of cement and RHA. Polypropylene (PP) fibers are also used to decrease the growth of tensile cracks and increase the overall strength of samples. As the main scope, effect of sand content (in different conditions: with and without presence of RHA) on the compressive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 32 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…A different study examined the dynamic behavior of sand stabilized with RHA in place of cement, and the results showed new correlations that could be used to evaluate the degradation index, shear modulus, damping, and unconfined compression strength. For the dynamic design of pile-supported foundations, those realizations are crucial [11][12][13]. Strengthening the Subgrade Soil's Mechanical properties -considerable mechanical upgrades have been determined in subgrade soil from a failed road section in Nigeria when RHA and cement kiln dirt (CKD) had been used in the research.…”
Section: Introductionmentioning
confidence: 99%
“…A different study examined the dynamic behavior of sand stabilized with RHA in place of cement, and the results showed new correlations that could be used to evaluate the degradation index, shear modulus, damping, and unconfined compression strength. For the dynamic design of pile-supported foundations, those realizations are crucial [11][12][13]. Strengthening the Subgrade Soil's Mechanical properties -considerable mechanical upgrades have been determined in subgrade soil from a failed road section in Nigeria when RHA and cement kiln dirt (CKD) had been used in the research.…”
Section: Introductionmentioning
confidence: 99%
“…Chen feng [10] concluded that basalt fiber can effectively improve the tensile strength and plastic deformation capacity of cement soil. Tang Chaosheng [11] proposed to use the physical reinforcement effect of polypropylene fiber combined with the chemical reinforcement effect of cement to discuss the influence of the content and length of polypropylene fiber on the strength of cement soil. He Wenxiu [12] used glass fiber and fly ash to improve the mechanical properties of cement soil.…”
Section: Introductionmentioning
confidence: 99%